2022
DOI: 10.1080/19490976.2022.2111950
|View full text |Cite
|
Sign up to set email alerts
|

Dual RNA-seq reveals a type 6 secretion system-dependent blockage of TNF-α signaling and BicA as a Burkholderia pseudomallei virulence factor important during gastrointestinal infection

Abstract: Melioidosis is a disease caused by the Gram-negative bacillus Burkholderia pseudomallei ( Bpm ), commonly found in soil and water of endemic areas. Naturally acquired human melioidosis infections can result from either exposure through percutaneous inoculation, inhalation, or ingestion of soil-contaminated food or water. Our prior studies recognized Bpm as an effective enteric pathogen, capable of establishing acute or chronic gastrointestina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…T6SS-1 effector proteins, such as Hcp1 (BPSS1498), which are important for MNGC formation, play important roles during infection ( 41 ). Recently, Sanchez-Villamil et al ( 42 ) identified virulence factors and regulatory proteins associated with T3SS-3 and T6SS-1 that are important for infection of intestinal epithelial cells. The authors noted that the BicA (BPSS1533) protein regulates both T3SS-3 and T6SS-1, as a Δ bicA mutant had reduced B. pseudomallei intracellular survival, reduced plaque formation, and impacted virulence in a murine model of gastrointestinal infection.…”
Section: Resultsmentioning
confidence: 99%
“…T6SS-1 effector proteins, such as Hcp1 (BPSS1498), which are important for MNGC formation, play important roles during infection ( 41 ). Recently, Sanchez-Villamil et al ( 42 ) identified virulence factors and regulatory proteins associated with T3SS-3 and T6SS-1 that are important for infection of intestinal epithelial cells. The authors noted that the BicA (BPSS1533) protein regulates both T3SS-3 and T6SS-1, as a Δ bicA mutant had reduced B. pseudomallei intracellular survival, reduced plaque formation, and impacted virulence in a murine model of gastrointestinal infection.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of T6SS-mediated pathogenesis and the impact that MNGC formation has on the host response is currently poorly understood. Previously, our laboratory sought to illuminate the impact of the T6SS on host response via dual RNA-seq in our in vitro model of GI infection (18). This analysis revealed that in the absence of the T6SS, there is substantial differential expression in pathways that are involved in inflammation, cell death, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The ligated DNA was transformed to E. coli S17-1 λpir donor strain. The upstream-BPSS1498-downstream/pMo130 plasmid was introduced into Bpm Δhcp1 strain by biparental mating as described elsewhere (18).…”
Section: Construction Of Hcp1 Strain Complementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing a library of transposon mutant and isogenic mutants demonstrated deletion of the bicA gene of B. pseudomallei, which encodes a putative T3SS/T6SS regulator, significantly impacts the bacteria's survival and virulence in acute and chronic gastrointestinal infections. 4 The cluster 1 type VI secretion gene, BPSS1504, is known to enhance the intracellular virulence of B. pseudomallei. 5 Our understanding of the virulence due to the regulation of such molecules is of utmost importance in comprehending how this adaptable pathogen modulates its lifestyle.…”
mentioning
confidence: 99%